OPTIMALISASI PERAN KUD NELAYAN DALAM MEWUJUDKAN KETAHANAN EKONOMI KELUARGA (Studi Kasus Pada Nelayan di Desa Surya Bahari Kecamatan Paku Haji Kabupaten Tangerang Banten) - , WIDIGDHO, Dr. Armaidy Armawi, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Cooperative is one of the economic institutions that are expected to perform tasks such as credit, savings and loans, credit insurance, provision and distribution of the means of production of daily necessities and other services, management and marketing of production and other economic activities required by members . In the presence of cooperatives is expected to improve the welfare of fishing communities in the village of Haji Solar Nails Maritime District, District of Tangerang, Banten. The research method was a study that aims to describe, illustrate a phenomenon that became the object of research in KUD Mina ocean to increase the income of the fishermen community members to realize the Family Economic Security. Qualitative research in a way that is with reference to case studies and jump directly to make observations and interviews with involved directly with the object studied in the location. From the results of research on optimization role KUD Mina Bahari Surya Ocean Village can be concluded that in order to increase the income of fishermen, the policy required the cooperative leadership of the regulatory changes in the savings and loan cooperatives for members of fishing cooperatives, human resource development through courses conducted for the members of fishing cooperatives and grow a business climate conducive to hard work, discipline and honesty and openness through increased mastery of technology, information, membership of cooperatives in order to improve the quality of family income. In addition, the need for policies and the implications of cooperative leadership in improving public confidence in the KUD Mina ocean fishing that the cooperative will seek to serve members better fishing cooperatives and full of honesty and transparency in the management and distribution of SHU to members of the cooperative. It will have an impact on increasing the income of fishermen so that they can lead to economic sustainability of fishing communities with good families.